Mass spectrometry imaging-based explainable machine learning reveals the biochemical landscapes of the mouse brain - Gildenblat, Jacob; Stamnas, Jorunn; Pahnke, Jens (Free Neuropathology, 2026)
Recent computational advances in mass spectrometry imaging (MSI) now enable unprecedented insight into organ-wide molecular composition and functional architecture. Here, we present the first high-resolution molecular-computational atlas of specific mouse brain lipids and metabolites, acquired using a NEDC matrix and negative-mode MSI, covering 123 anatomically defined regions and 191 polygonal annotations derived solely from MSI data, without auxiliary imaging. To overcome annotation ambiguity and MSI complexity, we introduced the Computational Brain Lipid Atlas (CBLA), a graph-based visual-explainability framework that generates Virtual Landscape Visualizations (VLVs) of specific lipid distributions across brain substructures. The CBLA integrates dimensionality reduction and ensembles of supervised models to (i) refine annotations, (ii) elucidate interregional relationships, (iii) interpret model behavior, and (iv) formulate biologically testable hypotheses. The CBLA revealed novel lipid distribution patterns, functional integrations, anatomical connections – the brain's telephone cables, and region-specific disease signatures – index lipids, including disease networks in the basal ganglia. It further identified index lipids that trace extrapyramidal nuclei and their cortical-brainstem connections, highlighting network-level molecular organization. A new algorithm decomposes annotated regions into precise mass-to-charge (m/z) features and resolves high-resolution m/z values from MSI data, m/z producing a comprehensive high-resolution brain map. It can be applied to any MS measurements, including metabolites, lipids, and peptides. This resource underpins downstream studies, as exemplified here by characterizing the molecular lipid composition of Aβ plaques in APP and ABCA7 transgenic mice, their spatial arrangement, and their connections with surrounding tissue. For the first time, our data suggest that GM3 ganglioside accumulation in cortical amyloid plaques may originate from hippocampal structures, consistent with longstanding evidence of disrupted hippocampo-cortical connectivity; a similar origin may also apply to plaque-associated Aβ signals in the cortex. More broadly, several selected m/z signals showed putative anatomical origins in specific brain subregions. Together, these findings establish MSI-ATLAS as a general framework for mapping brain organization and disease-related molecular networks directly from MSI data.